Design and Initial Testing of Augmented Reality Learning Media for Manufacturing Engineering Drawing Materials - Saputra, Tri Hannanto; Ismadi, Ignatius Henry; Hapsari, Fransiska Karlentina; Nugroho Cahyo Widodo, Petrus Iwan; Prasetyo, Benedictus Alvin; Aditomo, Muhammad Amin (STMIK Widya Cipta Dharma, 2025)
The rapid development of the manufacturing industry requires vocational graduates to possess high competence in technical drawing literacy according to the International Organization for Standardization (ISO). However, students often face cognitive barriers in visualizing 2D technical drawing representations into 3D forms, particularly in orthogonal projection and section view materials. This study aims to design and conduct initial testing of an Augmented Reality (AR)-based learning medium developed using the Rapid Application Development (RAD) method. The application is built on the Android platform using Unity 3D marker-based tracking method. This research produced a prototype application capable of projecting 3D models of machine components in real-time on top of printed technical drawing modules. Initial testing was conducted using the Black Box Testing method to validate system functionality. Test results indicate that key features such as marker detection, interactive object rotation, and visualization of hidden lines ran successfully under various lighting conditions. This application offers a potential solution to reduce students' cognitive load in understanding abstract spatial concepts.